Comparation of two cystatin C-based eGFR equations in assessing risk of all-cause mortality and incident cardiovascular disease - Guangda Xin; Qianyu Li; Chen Sheng; Yining Zha; Kailiang Cheng (Nutrition & Metabolism)
Abstract Background Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) 2021 and European Kidney Function Consortium (EKFC) 2023 both recently updated the equations to estimate the glomerular filtration rate (eGFR) using cystatin C; however, little is known about the benefits of using the equations for the risk stratification of health outcomes. We conducted this longitudinal study to compare the cystatin C CKD-EPI and EKFC equations to track the risks of cardiovascular disease and all-cause mortality among Chinese adults. Methods We used data from China Health and Retirement Longitudinal Study (CHARLS) between 2011 and 2018. Adjusted logistic regression models and restricted cubic spline functions were used to evaluate the relationships of cystatin C-based eGFR values with incidence of cardiovascular disease and mortality. Results A total of 6 496 participants were finally included in this study. The mean age of the participants was 59.6 (± 9.5) years, including 2996 (46.1%) males. There were 473 deaths and 1996 cases of cardiovascular disease observed during a maximum follow-up of 7.0 years. Using cystatin C-based CKD-EPI equation, people of eGFR < 60 mL/min/1.73 m2 had an increased risk of mortality (risk ratio [RR], 1.527; 95% CI, 1.068–2.178) and incident cardiovascular disease (RR, 1.363; 95% CI, 1.006–1.844), compared to those of eGFR ≥ 90 mL/min/1.73 m2. On the contrary, we did not observe significant associations of eGFR levels by EKFC equation with mortality nor cardiovascular disease. Conclusions The findings indicated that cystatin C-based eGFR using CKD-EPI equation is more closely associated with all-cause mortality and cardiovascular disease compared to EKFC equation among Chinese adults. The cystatin C-based eGFR by CKD-EPI equation should be monitored in health practice, which needs further validation in other populations.